Kemampuan Kebertahanan Masyarakat pada Permukiman Rawan Banjir di Kecamatan Barabai, Kabupaten Hulu Sungai Tengah - Madalia Indrasari; Iwan Rudiarto (Jurnal Wilayah dan Lingkungan, 2020)
Seasonal floods that occur in residential areas affect the socio-economic conditions of the community which will gradually lead to a level of survival. Resilience occurs because of the encouragement of the community that exposed to flood disasters to absorb and overcome the disturbances and get recover to keep continue the life, including to the community who live in flood-prone settlements in Barabai District. This study aims to analyze the ability of community survival as resilience in flood-prone areas in Barabai District. The method used in this research is quantitative descriptive with scoring method whose assessment is based on the Resilience Radar index. This research asseses the social, economic, preparedness and physical dimensions. The results of the study found that the high-resilience element of the community resilience in Barabai is social dimension, and the low-resilience element is physical dimension. In aggregate, the community in flood-prone settlements in Barabai has a medium level of survival capability to flood disaster.